2006
DOI: 10.1007/s10433-006-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical performance among high-functioning older adults: a 6-year follow-up study

Abstract: Purposes of the study were (1) to investigate changes in physical performance during 6 years followup among high-functioning older adults and (2) to describe the selection of study sample with reference to measured performance. Subjects (n=1,133) born during 1917-1941 participated in the battery of health-related fitness (HRF) tests (6.1-m walk, stair climbing, backwards walk, trunk side-bending, dynamic back extension, 1-km walk and body mass index) in 1996. Six hundred and six subjects were retested in 2002.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Assessment of HRF, in 1996, was conducted by selected test items of validated HRF tests targeted at high-functioning older adults. 17,21,22,29 The original test battery includes measurements of all main components of HRF. 25 The time requirement for one person to complete all tests is relatively high, taking about 60 minutes.…”
Section: Assessment Of Health-related Fitnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of HRF, in 1996, was conducted by selected test items of validated HRF tests targeted at high-functioning older adults. 17,21,22,29 The original test battery includes measurements of all main components of HRF. 25 The time requirement for one person to complete all tests is relatively high, taking about 60 minutes.…”
Section: Assessment Of Health-related Fitnessmentioning
confidence: 99%
“…During the six years follow-up time 135 (20%) subjects were lost to follow-up because they could not be contacted (n=62), refused to respond to the follow-up questionnaire (n=67), or had severe health restrictions (n=6) 22 . Our previous study 17 showed that poorer baseline (1996) performance in HRF tests increased the risk for non-response at follow-up (2002). The analyses of the present study included 537 subjects who responded to the questionnaire in…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our former study among the current study population showed that side-bending flexibility decreased during 6 years of follow-up, especially in the older age groups. 18 Thus, among older adults reduced lateral flexibility may be an important risk factor for BP, even though the findings on younger adults are mainly negative.…”
Section: Musculoskeletal Fitnessmentioning
confidence: 97%
“…Assessment of HRF was conducted by the proposed battery of HRF tests targeted at high-functioning older adults. 14,15,[17][18][19] The battery includes measurements of all main components of HRF, which provides applicability in physical activity counseling. The individual test results can be used in targeting physical exercise at those components of HRF that need to be improved for maintaining and improving mobility and back function.…”
Section: Assessment Of Health-related Fitnessmentioning
confidence: 99%